On the Extent of Linkage Disequilibrium in the Genome of Farm Animals - Qanbari, Saber (Frontiers in Genetics, 2020)
Given the importance of LD in gene mapping and evolutionary inferences, I characterize in this review the pattern of linkage disequilibrium (LD) and discuss the influence of human intervention during domestication, breed establishment and subsequent genetic improvement on shaping genome of livestock species. To this end, I summarize data on the profile of LD based on array genotypes vs. sequencing data in cattle and chicken, two major livestock species, and compare to the human case. This comparison provides insights into the real dimension of the pairwise allelic correlation and haplo-block structuring. The dependency of LD on allelic frequency is pictured and a recently introduced metric for moderating it is outlined. In the context of the contact farm animals had with human, the impact of genetic forces including admixture, mutation, recombination rate, selection and effective population size on LD is discussed. The review further highlights the interplay of LD with runs of homozygosity and concludes with the operational implications of the widely used association and selection mapping studies in relation to LD.